Safety Assessment of Marketed Medicines (SAMM) studies: Problems addressed but problems raised? - Ayres, J; Frost, C; Holmes, W; Venables, K; Ward, S (2002)
SAMM studies, when properly conducted, can provide rapid accrual of safety data for the regulatory authorities, the pharmaceutical company and health care professionals. Results should be made widely available, either through peer-reviewed papers or on the web. A SAMM PMS study should include a comparator group but the question of randomization remains open to discussion. If randomization is decided upon, the study should be submitted for ethical review, but the ethics committees must be aware of the SAMM guidelines when considering the science of the application. In our view randomization may not be necessary provided the primary outcome variable on which the sample size is based is robust to differences in severity in the populations being compared.